Functional capacity assessment instruments in post-Covid 19 patients: a systematic review (Research, Society and Development, 2023)
“Long Covid” is the term used to describe an illness found in people who have recovered from Covid 19 but still report lasting effects of the infection or the usual symptoms for much longer than expected. The treatment of this condition aims to improve functional capacity, increase quality of life, facilitate social reintegration after hospitalization, reduce fatigue, dyspnea, ageusia and improve the ability to perform daily activities. As the evaluation is of paramount importance for the conduct of the treatment, the objective of the present study was to identify, characterize and classify the instruments for evaluating the functional capacity of patients affected with Covid Longo. In this way, searches were carried out in the PEDro, COCHRANE and PubMed databases, using the descriptors: “Long Covid”, “Post Covid syndrome”, “functional capacity”, “sequels Functional capacity tests” associated through the Boolean operators “AND” and “OR”. 101 articles were obtained through searches in the bases, soon after applying the inclusion and exclusion criteria, 6 studies were included for analysis. Through the analysis of the works, 20 evaluation instruments were identified divided between scales, questionnaires and functional tests that transit in the specialties of cardiorespiratory, neurological and musculoskeletal evaluation, aimed at the management of the post-Covid 19 patient. It is concluded, therefore, that there are a variety of assessment instruments for the management of post-Covid patients, with a prevalence in cardiopulmonary assessment. In addition to the respiratory part, in the musculoskeletal assessment domain, the most used instrument was the handgrip test by dynamometry.